Radiation exposure of aircrews due to Space Radiation - Tezari, A.; Paschalis, P.; Gerontidou, M.; Mavromichalaki, H.; Karaiskos, P. (HNPS Advances in Nuclear Physics, 2019)
Space radiation mainly consists of trapped particles inside the Earth’s magnetosphere, galactic and solar cosmic rays. Cosmic rays propagating in the interplanetary medium, reach the top of the Earth’s atmosphere and collide with the molecules of the atmospheric layers creating showers of secondary particles that can be recorded by ground-based neutron monitors or muon detectors. Due to these cascades, the radiation environment in various atmospheric altitudes is entirely different than the one experienced on the Earth’s surface. Space radiation is ionizing (trapped particles, galactic and solar cosmic rays) as well as non-ionizing (ultra-violet radiation). It is known that ionizing radiation is very dangerous for all biological systems, causing a variety of acute and chronic effects. The determination of the occupational exposure of aircrews to space radiation is of great importance. DYnamic Atmospheric Shower Tracking Interactive Model Application (DYASTIMA), as well as its extension DYASTIMA-R, is a standalone application, based on the toolkit Geant4, that simulates the propagation of cosmic radiation into the atmosphere. DYASTIMA provides all the necessary information about the study of the cascade in different atmospheric altitudes, while DYASTIMA-R, as a dosimetry application, calculates radiobiological quantities, such as dose rate and equivalent dose rate for the determination of the exposure, based on the output provided by DYASTIMA. These quantities are calculated for solar minimum and solar maximum conditions. DYASTIMA can be accessed through the portals ofthe European Space Agency (ESA) (http://swe.ssa.esa.int/spaceradiation) and the Athens Neutron Monitor Station (A.Ne.Mo.S) (http://cosray.phys.uoa.gr/index.php/dyastima).